2013
DOI: 10.1371/journal.pone.0079306
|View full text |Cite
|
Sign up to set email alerts
|

Neuropilar Projections of the Anterior Gastric Receptor Neuron in the Stomatogastric Ganglion of the Jonah Crab, Cancer Borealis

Abstract: Sensory neurons provide important feedback to pattern-generating motor systems. In the crustacean stomatogastric nervous system (STNS), feedback from the anterior gastric receptor (AGR), a muscle receptor neuron, shapes the activity of motor circuits in the stomatogastric ganglion (STG) via polysynaptic pathways involving anterior ganglia. The AGR soma is located in the dorsal ventricular nerve posterior to the STG and it has been thought that its axon passes through the STG without making contacts. Using high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 50 publications
2
16
0
Order By: Relevance
“…That said, at a finer scale of analysis, intracellular dye-fills of identified neurons in invertebrates show clear evidence of animal-to-animal variations in soma positions and branching patterns [27, 28, 29]. For example, a recent study of the Anterior Gastric Receptor (AGR) neuron in the crab stomatogastric ganglion (STG) shows large variations in the number of branches that AGR makes in the STG neuropil [28]. …”
Section: Variability In System Components Across Animalsmentioning
confidence: 99%
“…That said, at a finer scale of analysis, intracellular dye-fills of identified neurons in invertebrates show clear evidence of animal-to-animal variations in soma positions and branching patterns [27, 28, 29]. For example, a recent study of the Anterior Gastric Receptor (AGR) neuron in the crab stomatogastric ganglion (STG) shows large variations in the number of branches that AGR makes in the STG neuropil [28]. …”
Section: Variability In System Components Across Animalsmentioning
confidence: 99%
“…The AGR axon projects through the STG (Fig. 1A) and albeit no connections from AGR to descending projection neurons have been identified, Goeritz et al (2013) suggested putative chemical connections to an unknown modulatory projection neuron.…”
Section: Resultsmentioning
confidence: 99%
“…Distinct input pathways have been shown at times to activate similar gastric patterns and at other times to activate different versions of gastric rhythm, which depend on feedback projections back to the CoGs (Blitz and Nusbaum 2012;Saideman et al 2007;Wood et al 2000). Sensory inputs from the stomach are also important for shaping gastric activity both in the intact animal and in vitro (Beenhakker et al 2004(Beenhakker et al , 2005Blitz et al 2004;Combes et al 1995;Goeritz et al 2013;Hedrich et al 2011;Harris-Warrick 1989, 1991). Thus decentralization might represent a more dramatic perturbation for the gastric network than for the pyloric circuit.…”
Section: Discussionmentioning
confidence: 99%